How the Personal Profiles of US State Governors Impact on Financial Sustainability - Alcaide Muñoz, Laura; López Subires, María Deseada; Navarro Galera, Andrés; Rodríguez Bolívar, Manuel Pedro (My University, 2023)
This paper considers the extent to which the Governor’s profile might influence the financial sustainability of the State government, via an empirical study of 50 US States during the period 2006–2013. The results obtained show that financial sustainability may be prejudiced when the State government experienced financial unsustainability during the previous year, and when it is led by a Governor who is a Democrat, Black, and/or long serving. A favorable influence on financial sustainability is produced when the Governor is female, serving in his/ her home State, has children and has a college education. These findings highlight factors that should be considered with respect to promoting financial sustainability via public policies, providing valuable information to facilitate supervision by the State Legislature (General Assembly) and Supreme Audit Institutions. Moreover, these findings enable opposition parties and other stakeholders as citizens to evaluate the financial viability of electoral promises.
Keywords: Finanzas; Financial sustainability; Political factors; Governors’ profile